TINJAUAN YURIDIS SISTEM PEMBUKTIAN DALAM PENANGANAN TINDAK PIDANA KORUPSI DI INDONESIA - Gulo, Efermin; Siregar, Azhali; Ismaidar, Ismaidar (Ensiklopedia of Journal, 2025)
Abstract: Corruption is an inseparable part of human history and is among the oldest forms of crime, often regarded as one of the diseases of society, similar to other crimes such as theft, which have existed since the dawn of humanity. The main issue faced today is that corruption tends to increase alongside prosperity and technological advancement. Experience shows that as a nation's development progresses, people's needs and desires grow, and one of the consequences may be a greater tendency to commit corrupt criminal acts. This research employs a normative legal method, which refers to legal norms found in statutory regulations, literature, societal legal norms, and relevant data, all of which are analyzed to address the research problems. This study clearly aims to analyze the application of land laws, using a qualitative research approach conducted through examining legal literature and regulations related to the topic of "A Juridical Review of the Proof System in Handling Corruption Crimes in Indonesia." The legal process is essential in establishing an effective anti-corruption system; therefore, justice must be fairly enforced. Fugitive corruptors who flee abroad must be brought back to their home country and sentenced appropriately. Eradicating corruption is the most urgent issue that must be addressed in the nation, as it has significantly hindered national progress. Corrupt practices have become so widespread and appear to be beyond government control. However, efforts to combat corruption are frequently obstructed by various complex challenges. This crime can occur anywhere, meaning it is not limited by space, time, or race. It is closely related to laws and regulations within the legal field that are positively enforced. Punishment is an unpleasant consequence (suffering) imposed by a judge through a verdict upon individuals who have violated criminal laws. Keywords: System, Proof, Corruption Crime.